Systematic Review of Mammography Screening Educational Interventions for Hispanic Women in the United States - Luque, John S.; Logan, Ayaba; Soulen, Grace; Armeson, Kent E.; Garrett, Danielle M.; Davila, Caroline B.; Ford, Marvella E. (Journal of cancer education, 2019)
In the United States (U.S.), Hispanics experience breast cancer disparities. Breast cancer is the leading cause of cancer-related death among Hispanic women, and Hispanic women receive mammography screening at lower rates than some other ethnic groups. This low rate of screening mammography is associated with increased risk for possible late-stage diagnosis and lower survival rates. Educational interventions could play a role in increasing screening mammography rates among Hispanic women. This systematic review synthesized the current literature on educational interventions to increase mammography screening among Hispanic women. The review included studies published between May 2003 and September 2017 with experimental and quasi-experimental interventions to increase mammography screening among Hispanics in the U.S. Five studies out of an initial 269 studies met inclusion criteria for the review. All studies employed an interpersonal intervention strategy with community health workers, or promotoras, to deliver the mammography screening intervention. For each study, odds ratios (OR) were calculated to estimate intervention effectiveness based on similar follow-up time periods. The study ORs resulted in a narrow range between 1.02 and 2.18, indicating a low to moderate intervention effect for these types of interpersonal cancer education interventions. The summary OR for the random effects model was 1.67 (CI 1.24–2.26). Hispanics exhibit lower levels of adherence to screening mammography than non-Hispanic whites. Interpersonal cancer education interventions such as the use of promotoras may help to mediate the impact of barriers to receiving a mammogram such as low health literacy, deficits in knowledge about the benefits of screening, and low awareness of the availability of screening services.